Self-reported and accelerometer-measured physical activity by body mass index in US Hispanic/Latino adults: HCHS/SOL - P. Palta; R.G. McMurray; N.A. Gouskova; D. Sotres-Alvarez; S.M. Davis; M. Carnethon; S.F. Castañeda; M.D. Gellman; A.L. Hankinson; C.R. Isasi; N. Schneiderman; G.A. Talavera; et al. (Preventive Medicine Reports, 2015)
The association between obesity and physical activity has not been widely examined in an ethnically diverse sample of Hispanic/Latino adults in the US. A cross-sectional analysis of 16,094 Hispanic/Latino adults 18–74 years was conducted from the multi-site Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Body mass index (BMI) was measured and categorized into normal, overweight, and obese; underweight participants were excluded from analyses. Physical activity was measured using the 16-item Global Physical Activity Questionnaire and by an Actical accelerometer. Minutes/day of physical activity and prevalence of engaging in ≥150 moderate–vigorous physical activity (MVPA) minutes/week were estimated by BMI group and sex adjusting for covariates. No adjusted differences were observed in self-reported moderate (MPA), vigorous (VPA), or MVPA across BMI groups. Accelerometry-measured MPA, VPA, and MVPA were significantly higher for the normal weight (females: 18.9, 3.8, 22.6 min/day; males: 28.2, 6.1, 34.3 min/day, respectively) compared to the obese group (females: 15.3, 1.5, 16.8 min/day; males: 23.5, 3.6, 27.1 min/day, respectively). The prevalence of engaging in ≥150 MVPA minutes/week using accelerometers was lower compared to the self-reported measures. Efforts are needed to reach the Hispanic/Latino population to increase opportunities for an active lifestyle that could reduce obesity in this population at high risk for metabolic disorders.